Distribution of Cleft Lip and Palate at Cleft Lip and Palate Center Medical Faculty, Universitas Muhammadiyah Malang, Indonesia - Ruby Riana A; David S. Perdanakusuma; Retno Handayani (Institute of Medico-legal Publications Pvt Ltd, 2021)
Cleft lip and palate (CLP) and cleft palate (CP)are a common head and neck hereditary deformity. The highnumber of cases has prompted the Medical Faculty, Universitas Muhammadiyah Malang to start communityservice by providing free surgery to repair cleft lip and palate (Cleft Lip and Palate Center Medical Facultyof Universitas Muhammadiyah Malang (CLP MFUMM)).Purpose: To find the distribution of cases from the year of surgery, sex, side of CL/P, cleft palate (CP),hospital where the surgery was performed and parent education level in CLP MFUMM, from 2019 until2020.Patients and Methods: Two hundred and five consecutive cleft lip subjects, with or without palates, andcleft palate attending CLP MFUMM from 2019 until 2020 were studied.Results:The most surgeries done is at the year of 2019 (69%). Most of the patients were male (55%).CL/P were the most frequent cases (94%). Complete cleft found mostly in male patient with left unilateralcleft (23%), while incomplete cleft found mostly in female patient also with left unilateral cleft (7%). Thepalate involvement found mostly in soft palate only and female patients (46%). The surgeries were mostlyperformed at RSI Aisyiyah Malang (60%). The education level of the parents is mostly elementary school(father 36%, mother 34%).Conclusion: CL/P were the most frequent. Complete cleft mostly in male patient with left unilateral cleft,while incomplete cleft mostly in female patient also with left unilateral cleft. The cleft palate was mostlysoft palate only and female patients.